Quantitative evaluation of sea reclamation activities on tidal creek connectivity - Man, Ying; Zhou, Fangwen; Wang, Qing; Cui, Baoshan (Frontiers in Marine Science, 2023)
Deltas are in a dynamic balance due to the impact of fluvial and coastal flooding, and hydrological connectivity plays an important role. In recent decades, the dynamic equilibrium has been influenced by upstream and local human activities, including sea reclamation activities. However, in most instances, the influence of human activities has not been explicitly distinguished and quantified in detail. In this paper, the influence of sea reclamation activities on hydrological connectivity in the Yellow River Delta was quantified by parameterizing the resistance surfaces (a spatial layer that assigns a value to each landscape feature, indicating the degree to which that variable impedes or promotes movement) that includes sea reclamation activities. By optimizing a functional relationship between landscape features and hydrological connectivity (water flow movement patterns), the values in the resistance surfaces could be assigned. We first calculated hydrological distances among bifurcations from 1985 to 2020 with a 5-year interval representing the hydrological connectivity of each tidal creek. The sea reclamation activities in the YRD were classified into four: reclaimed land, sea enclosure activity, freshwater resource facilities, and engineering in the oil field to create resistance surfaces. We identified that the periods of 1990–1995 and 2000–2005 were under the most severe influence of sea reclamation activities. Sea enclosure activity, freshwater resource facilities, and engineering in oil fields played major roles in composing resistance surfaces. Mariculture (quantified relative resistance value, 1.00), reservoir (0.92), agriculture (0.91), and river (0.97) were the features with the highest resistance values in the initial and mature development stages. The formation of resistance (costs to movement) was due to human activities and natural factors, for example, the evolution of tidal creeks. To develop the resource in tidal flats sustainably, systematic monitoring and sufficient conservation awareness were required. This study contributed to coastal management and planning by providing a quantified assessment of different types of sea reclamation activities.